CINNAMOMUM BURMANNII PROTECTED HEPATOCYTES AND CORRECTED SERUM UREA AND URIC ACID LEVEL IN DIABETIC RATS. - Doti Wahyuningsih; Helmin Elyani; Dini Sri Damayanti; Muhammad Yusuf Musthafa; Vina Zahirotul Izzah (Published by Faculty of Medicine Universitas Islam Malang, 2017)
AbstractBackground. Hyperglycemia was reported to harm liver and induce metabolic inbalance. The tree bark of Cinnamomum burmannii (C. burmanii) was potential as anti-hiperglycemic agent. The bark was rich with secondary metabolites that may lead to possess other advantages for diabetes.Objectives. To study the effect of aqueos extract of C.burmannii (AEC) on liver and metabolic condition by measuring necrotic hepatocytes, serum urea and uric acid levels in alloxan-induced diabetic rats (AIDRs).Methods. Three groups of fasted rats (free allowed to water) were intraperitoneally injected with 150 mg/Kg BW in 1 ml normal saline 6 hours prior to intraperitoneal injection of 2 ml 10% glucose to induce AIDRs, the animals were allowed to 5% glucose solution for 24 hours afterward. The AIDRs were treated with 0.5 ml, 1ml, and 2 ml of AEC respectively for 2 weeks. Hematoxyline-Eosine-stained liver slices were observed for necrotic hepatocytes by light microscope. Serum urea and uric acid levels were measured by Glutamate dehydrogenase and Uricase-PAP methods respectively. Data were analyzed by ANOVA followed by LSD test, p values of < 0.05 were considered to be significant.Results.The given doses of AEC lowered urea and uric acid serum levels of AIDRs (p = 0.000) which approximated to the non diabetic ratss serum levels (p > 0.05). Except the smallest dose, the remaining doses of AEC reduced necrotic hepatocytes number in AIDRs (p = 0.000).Conclusion.Aqueos extract of C.burmannii protected hepatocytes and corrected serum urea and uric acid levels of alloxan-induced diabetic rats.Keywords: Cinnamomum burmanii; diabetes; necrotic hepatocytes; serum urea: serum uric acid.